SELISIH BIAYA PER 1 M3 PEKERJAAN STRUKTUR ANTARA BIAYA EE DAN BIAYA OLEH KONTRAKTOR SEBAGAI PEMENANG PELELANGAN PROYEK PEMBANGUNAN GEDUNG DI UNY DAN PROYEK PEMBANGUNAN GEDUNG PEMERINTAH LAINNYA DI DAERAH KABUPATEN SLEMAN YOGYAKARTA TAHUN 2012 - - Bada Haryadi (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2014)
This research aims to (1) To know how the difference between the cost of percent or as the cost of per m3 concrete work which includes foot plate fondation; sloof; column, beam and plate The building offered by the UNY as Owner Estimate (OE) Who was approved for the implementation of the project with the cost of per-m3. (2) find out what percentage difference in cost or unit price per m3 of concrete work that includes foot plate fondation; sloof; column, beam and plate, the building offered by the owner outside of UNY in Sleman Regency (OE/EE) approved for implementation of the work with a unit price per 1 m3 of concrete work, Which includes work foot plate, sloof, column, beam and plate the floor Offered by the contractor as a winner prequalification 2012. The population of this research are all building procurement documents that include unit price analysis (per-m3 concrete work) Possessed providers (owner) and providers (contractor) that job has been building structures of Government or other institutions in the area of Sleman Regency, Daerah Istimewa Yogyakarta (DIY) in 2012. The samples were taken as much of the document procurement contractors to a building owned by Universitas Negeri Yogyakarta (4 building) and 5 building in the area of Sleman Regency, and Daerah Istimewa Yogyakarta (DIY) in 2012. The data obtained were analyzed using qualitative, descriptive methods, namely data research results in the field didiskripsikan is associative. The results of this research are (1) The difference in average cost per 1 m3 of concrete work, which consists of the work foot plate fondation, sloof, columns, beams and floor plate between the costs offered UNY (EE) and costs from contractors who get a job (the winner of the prequalification) building in UNY is reasonable with (13,6% 15%); (2) The price difference/average cost per 1 m3 of concrete work, which consists of the work foot plate fondation, sloof, columns, beams and floor plate between the cost of the owner (EE) and costs from contractors who get a job building outside of UNY in Sleman, Yogyakarta is still can be said quite reasonable with (21,4% 20%).Key word: cost estimate, owner, contractor